Peran Dosen dalam Mengembangkan Karakter Mahasiswa - Markus Masan Bali (Humaniora, 2013)
Character building education today is non-negotiable for the character building of students in college. One important element in the character education of students in college is lecturers. Lecturers have an important role in character education in college. In carrying out the main task of the Tri Dharma University, which is doing the teaching, research, and community service, a lecturer does a process of internalization of the noble values which later become the campus culture. Lecturers are the main actors in the formation and development of the students’ character with exemplary. Before educating the students’ character, a lecturer at least has the character corresponding to the main task of a teacher. In addition, a very important role of which is not overlooked is to educate, teach, train, guide, and evaluate.